ALIRAN EKSISTENSIALISME DALAM PANDANGAN FILSAFAT PENDIDIKAN ISLAM - Adawiah, Rabiatul (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
Existentialism is a philosophy that emphasizes on individual existenceand self-fulfillment. Each individual is seen as being unique, and musttake personal responsible for his fate. Existentialism is closely related toeducation because they both talk about the same issues, such as humanlife, human relations, the nature of personality, and freedom. Islam viewsthat humans have potentials to be developed since the day they were born.Islam gives a very noble position to humans. The ultimate goal of Islamiceducation is striving to realize a perfect individual muslim who can carryout its function as an abid and caliph on the earth.